Estimation of Natural Uranium and Its Risk-Assessment in Groundwater of Bangalore Urban District of Karnataka, India - Naik, Poojashri Ravindra; Alurdoddi Rajashekara , Vinod; Mudbidre, Rajalakshmi (Geomatics and Environmental Engineering, 2024)
In this study, 56 groundwater samples were taken from diverse sources in Bangalore Urban district during the pre-monsoon and post-monsoon seasons to measure the uranium concentration and its correlation with different waterquality parameters. The uranium concentration varied from 0.94–98.79 µg/L during the pre-monsoon season and from 1.38–96.52 µg/L during the postmonsoon season. Except for a few readings, all were within the safe limit of 60 µg/L as prescribed by India’s Atomic Energy Regulatory Board (AERB), Department of Atomic Energy (DAE). Owing to its slightly higher concentration, a study on the radiological and chemical risks that are caused due to the ingestion of uranium was assessed. Based on the radiological aspect, cancer mortality and its risks were assessed, wherein all of the samples were well within the acceptable limit of 10−4; therefore, consuming these water samples was radiologically safe. However, when the risk that was caused by chemical toxicity was assessed, a few samples exceeded the hazard quotient (HQ) value of more than 1, thus illustrating that individuals were vulnerable to chemical risk. This paper features assessments of uranium and its risks to public health in groundwater samples if it exceeded the safe limit. Additionally, it recognizes the value of periodically assessing and treating the area’s drinking water sources.